The Impact of Hedging on Firm Value of Public Non-Bank State-Owned Enterprises - Henny Galla Pradana; Prima Naomi (Jurnal Keuangan dan Perbankan, 2018)
This research aimed to find the impact of hedging on firm value. This research focused on 14 public non-bank state-owned enterprises listed in Indonesia Stock Exchange. The data used were quarterly data from 2011 to 2015, and panel data analysis. The basic model of research used referred to the research of Júnior Laham (2008) as well as the development of models conducted by Allayanis Weston (2001) to correct endogenous factors. The results showed that only five of the fourteen state-owned corporations that used a hedging instrument. The research findings showed that the firms which did hedging had a higher value than a firm that did not do it. A more detailed investigation found that the adoption of hedging strategies could increase the firm value, and the dislocation of the hedging strategy had a negative effect on the firm value, compared to firms that kept implementing hedging strategy. The magnitude of hedging measured using the Total Notional Value of Derivative to Total Assets (TNVD) also had a positive impact on the firm value. This finding also supported Bank Indonesia Regulation Number 15/8/PBI/2013 which was effective in reducing exchange rate risk for state-owned enterprises which in turn increased the firm value.JEL Classification : G 2 1, G 28 , G3 2, G38DOI: https://doi.org/10.26905/jkdp.v22i2.1967